Comparison of CPU Scheduling Algorithms: FCFS, SJF, SRTF, Round Robin, Priority Based, and Multilevel Queuing - Pemasinghe, Sajeewa; Rajapaksha, Samantha (IEEE Region 10 Humanitarian Technology Conference (Online), 2022)
In this article, we are discussing various aspects of CPU scheduling. We first introduce the concept of CPU scheduling, different types of schedulers and the typical terminology used in relation to processes. Scheduling criteria, the optimization of which is the ultimate goal of a CPU scheduling algorithm, are also discussed. We then discuss various types of research studies that have been carried out with respect to CPU scheduling algorithms. Different CPU scheduling algorithms are examined with examples to highlight their characteristics. Advantages and disadvantages of each of these algorithms are also explored. The scheduling algorithms discussed are, first come first served, shortest job first, shortest remaining time first, priority based, round robin, multilevel queue, and multilevel feedback queue.